Ozone and nitric oxide interaction in Arabidopsis thaliana: A role for ethylene? - Ahlfors, Reetta (Landes Bioscience, 2009)
Nitric oxide (NO) is involved together with reactive oxygen species (ROS) in the activation of various stress responses in plants. However, the biochemical mechanisms by which ROS and NO participate, and the potential interaction between these molecules are still unclear. Ozone (O(3)) can be used as a tool to elicit ROS-activated stress responses and to activate cell death in plant leaves. We have recently shown that O(3) induced a rapid accumulation of NO in Arabidopsis leaves and at late time points NO production coincided with the formation of hypersensitive response like lesions.1 Experiments using O(3) and the NO-donor SNP alone or in combination indicated that both molecules are capable of activating a large set of stress related genes. In combined treatment, NO attenuated O(3)-induction of salicylic acid (SA) biosynthetic and signaling genes, and reduced SA accumulation. In addition, NO can elevate the levels of ethylene in several mutants. Thus, NO is a modifier of ROS signaling.